Migration out of rural areas and implications for rural livelihoods - de Brauw, Alan (Annual Reviews, 2019)
Despite the fact that migration out of agriculture has always been a part of the economic development process, policy makers have long feared that migration from rural areas reduces agricultural production. This article reviews the growing microeconomic literature with more credible statistical identification that evaluates the effects of migration on agricultural production and other outcomes among rural households. By and large, migration does not negatively affect agricultural production, as households shift on one of several margins to reduce the lost labor impact. Through migrant remittances, migration can lead to one of several different types of investment. When investment occurs, the type of investment depends upon relative local returns to investments in agriculture, nonagriculture, or human capital. Some innovative recent work also documents the role of migration in catalyzing technical change. Future policy related to rural out-migration should focus on enhancing its positive effects and mitigating any negative ones.